Cameroon : 2007 Article IV Consultation, Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criterion, Request for Modification of Performance Criterion, and Financing Assurances Review; Staff Report; Staff Supplement and Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that a number of factors have constrained Cameroon's growth potential relative to the group of lower-middle-income economies, including lower investment rate, shallower financial depth, less open trade; weaker infrastructure and human capital base; and weaker business environment. Growth picked up somewhat in 2006, following a rebound in construction activities, oil output, and forestry production. The outlook for 2007 and the medium term is encouraging. Economic activity is expected to pick up further in 2007, reflecting stronger performance in the forestry, construction and tertiary sectors.